Preparation of future development scenarios of urban landscapes in accordance with natural and socio-economic conditions (on the example of the cities of the Kura-Araz lowland) - Amanova, Shahnaz; Hajiyeva, Afag; Jafarova, Firuza (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
Problems Statement and Purpose. More than 50% of the world’s population lives in cities. In Azerbaijan, 53% of the population lives in cities. For this reason, almost all global problems originate from urban landscapes. Therefore, it is very important to study the development of cities and prepare the future scenario. Our goal is to study the cities located in the Kura-Araz plain, determine their annual growth rate and forecast future development trends. Data and Methods. In the article, the development of 17 cities located in the Kur-Araz plain in the central part of Azerbaijan during the historical period and its future forecast were analyzed. Modern methods were especially preferred during the research. Satellite images of cities were processed and the results were analyzed. Satellite images from 1975 and 2023 were used and deciphered in determining the boundaries of cities and studying their dynamics. The dynamics of changes in the areas of the cities were studied by determining the boundaries of the cities, and the dynamics of population growth was studied and analyzed. Statistical analyzes were used in the study of the population. Results and Discussion. The cities of Kura-Araz lowland cover 25% of the cities of the republic. These rivers are the main source of the formation of cities. However, as these coastal cities grew, the ecological problems of the Kura and Araz rivers increased and the water level decreased. Cities have grown in all directions and are still growing. For the first time in Azerbaijan, urban landscapes were studied based on GIS technologies and Remote Sensing methods. For the first time, the factors of natural conditions, the absolute height, inclination and exposure of the terrain were analyzed based on GIS technologies, and it was determined that 2/3 of the research area is located below sea level, and 1/3 is located in areas up to a maximum of 200 m absolute height. The inclination of the area continues up to a maximum of 5⁰. Cities have been classified in different directions. Conclusion. For the first time, issues of territorial management of urban landscapes were conducted and mapped on the basis of GIS technologies. At this time, it was determined that cities have grown more than 2 times during 1975-2023. However, this increase cannot be compared with the dynamics of population growth. Because during these years, the population growth has varied between 10-30%. Urban landscapes have grown mainly in riverside areas, along transport routes.